The Impact of Green Product Innovation, Green Perceived Quality to Purchase Intention Moderated by Lifestyle on Stainless Steel Straw - Lily Suhaily; Syarief Darmoyo; Sinta Boentoro; Eleonaora Anasthashia (International Journal of Applied Business and International Management, 2020)
The purpose of this study was to determine the effect of green product innovation, green perceived quality to purchase intention moderated by lifestyle on stainless steel straw. There is a direct influence of green product innovation, green perceived quality, and life style to purchase intention. Lifestyle does not moderate the relationship between green product innovation and purchase intention. However, lifestyle moderates the relationship between green perceived quality and purchase intention. Based on the results, restaurants and cafes should use stainless steel straws because the consumers have a lifestyle with the perception that eco-friendly products can reduce the impact of environmental pollution therefore, they intend to visit restaurants and cafes that use stainless steel straws.